Natural dye products business plan - Nor Ashikin, Abdul Hamid (2013)
Today dyeing is important and popular amongst natural loving and health awarded people. Nearly all dyes are currently produced from synthetic compounds. This means that costs have been greatly reduced and certain applications for enhanced. Customers more aware of environmental issues are now demanding natural products, naturally sourced. If a fashion company introduces a new line of clothes produced with a natural fibre, the naturally sourced dye is needed to complete the green label. Natural dyes can offer not only a rich and varied source of dyes, but also the possibility of an income through sustainable harvest of the dye plants. They also have a far superior aesthetic quality, which is much more pleasing to the eye. The company has developed to market the natural dye products to replace the synthetic dye that is harmful to workers during handle the work progress and for human skin to avoid from irritation and sensitive. This company has been given the name as a Natural Dye KKE Enterprise (NDKKEE). NDKKEE has mainly focused on textile industries that produce batik and clothing. The target market is divided into the domestic market and international market. The domestic market is included Pahang, Kelantan, Terengganu, Johor and Selangor while the international market will focuses on South Asia, U.K, U.S.A, Germany, India and Italy. The competitive position of our company is quite strong since the Malaysia has no competitors, thus need us to compare with the competitors from outside country mostly from China, India and U.K. Our company has the strength and advantages to compete with those competitors. The objectives and mission of our business are to expand the market into the local and international market, to maximize the profit and sustain the financial growth, to reduce the risks and uncertainties and to achieve the customer demand. The mission of our company is to produce the variety types of colors that can be compete to the other competitors and to take full advantage of ever increasing market trend of natural dye production.NDKKEE is a joint venture owned by 4 shareholders who also the major investors in NDKKEE. The management and organization in our company has 4 types of top management. The Chief Executive Manager is Dr. Wan Rosli Bin Wan Sulaiman. He has the highest percentage sharing in the company about 40%. The other management team are Marketing Manager, Operation Manager and Financial Manager who invest about 20% of each person in the company. The business plan is implemented to apply the loan from the bank about RM 1,000,000. The total investment was RM 500, 000 and the total capital cost budget is RM 1,500,000. Price per kilogram of natural dye products is RM 80.00. The Sales Projection, Profit and Loss Statement, Cash Flow and Balance Sheet shows the positive increment in the financial plan. The net profit of our company is RM 182,081 for the first year and RM 1,013,170 for the fifth year. The Payback Period of our company is expected to be 3.1 years approximately.